CARRIER THALASSEMIA: RISK ANALYSIS AND PRELIMINARY SCREENING USING SIMPLE LABORATORY TESTS AMONG BIOLOGY STUDENTS OF UNIVERSITAS RIAU - Yeni Etma Nazar; Titrawani Titrawani; Zulpadrianto Zulpadrianto; Ainul Mardiah; Nur Ikhlas Syuhada; Feni Andriani; Laila Ainur Rohmah; Syafrizal Syafrizal (BioCONCETTA, 2025)
Thalassemia is an autosomal recessive genetic disorder that remains a significant public health concern in Indonesia; consequently, early detection of carriers is crucial to prevent the birth of children with thalassemia major. This study aims to analyze the risk of thalassemia among Biology students at the Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Riau, utilizing a simplified laboratory screening approach. The research involved 30 students who participated in genetic risk questionnaires, hemoglobin level assessments using digital hemometers, and erythrocyte counts via hemocytometers. The findings revealed a questionnaire risk score of 0.07 (categorized as very low), a mean hemoglobin level of 12.73 g/dL, and an erythrocyte count of 5.22 million cells/µL, both of which fall within normal physiological ranges. These results indicate that the risk of thalassemia among Biology students at FMIPA Universitas Riau is remarkably low. Simple screening through questionnaires, hemoglobin levels, and erythrocyte counts can serve as an effective method for both educational purposes and the preliminary screening of thalassemia carrier risk in students.